2016
DOI: 10.1002/ccd.26781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of percutaneous coronary intervention in patients turned down for surgical revascularization

Abstract: PCI in a broad population of surgically ineligible patients is generally safe. However, among patients who underwent unprotected left main PCI, those deemed surgically ineligible experienced significantly worse outcomes as compared to the rest. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Some patients with an indication for CABG are deemed inoperable and subsequently referred for PCI. While registry data have shown that PCI of surgically ineligible patients is generally safe, the clinical characteristics and outcomes of these patients have not been well described 5 . The goal of this single‐center study is to describe the characteristics that contributed to ineligibility and determine the early and one‐year outcomes of this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with an indication for CABG are deemed inoperable and subsequently referred for PCI. While registry data have shown that PCI of surgically ineligible patients is generally safe, the clinical characteristics and outcomes of these patients have not been well described 5 . The goal of this single‐center study is to describe the characteristics that contributed to ineligibility and determine the early and one‐year outcomes of this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that registries are usually not well designed to characterize surgically ineligible patients and often do not capture the reason for ineligibility [1214]. McNulty et al addressed the limitations of registries for adequate documentations of surgical candidacy and selection biases in nonemergent LMCA stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that surgical ineligibility is associated with increased mortality in patients undergoing PCI on a diseased unprotected left main coronary artery (ULMCA) [12, 13]. More recently Sukul et al demonstrated in a larger study no difference in outcomes between surgically ineligible patients and the rest of the patients who underwent PCI, except in the subgroup of patients who underwent PCI on ULMCA [14]. In these patients, surgical ineligibility was associated with significantly higher and unacceptable in-hospital mortality as high as 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that registries are usually not well designed to characterize surgically ineligible patients and often do not capture the reason for ineligibility [12][13][14]. McNulty et al addressed the limitations of registries for adequate documentations of surgical candidacy and selection biases in nonemergent LMCA stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that surgical ineligibility is associated with increased mortality in patients undergoing PCI on a diseased unprotected left main coronary artery (ULMCA) [12,13]. More recently Sukul et al demonstrated in a larger study no difference in outcomes between surgically ineligible patients and the rest of the patients who underwent PCI, except in the subgroup of patients who underwent PCI on ULMCA [14]. In these patients, surgical ineligibility was associated with significantly higher and unacceptable inhospital mortality as high as 20%.…”
Section: Journal Of Interventional Cardiologymentioning
confidence: 99%